Language, Societal Security and Stability: A Study of the Expressive Forms used by Influential People on Television Programmes in Nigeria and the Republic of Congo: linguistique (Cahiers Africains de rhétorique, 2025)
This article studies the impact of the language of influential people on social security and stability in Nigeria and the Republic of Congo.  It explores the scope of hate speech, the use of vulgar language, derogatory family expressions, slang and insulting words from certain authorities and their consequences in the interest of the population.  The data to support the research was randomly selected and collected from the Nigerian television programme “Politics Today” and the Congolese national television programme. It reveals in the light of  Mead’s (1934) ‘Symbolic Interactionalism’ and Sacks’ (1992) ‘Conversational analysis’ that the state of each society is determined by the positive or negative roles played by language. Therefore, appropriate words uttered in pleasant tones and good dispositions (in spoken, written and sign language) can help strengthen the security and stability of a society.However, inappropriate language use is one of the potential causes of insecurity and instability. Ultimately, this study recommends that members of society, especially the most educated, learn to choose convenient words, understand the components of language, interact and make perfect communications. Furthermore, they must meticulously and judiciously convey useful messages to the relevant authorities for diligent responses. Journalists or producers of television programmes should reserve the right to make judgments when presenting their programmes. In doing so, they will avoid negatively influencing viewers so that the security and stability of society can be maintained.